Analisis potensi sektor ekonomi di Kabupaten Tuban, Lamongan, dan Bojonegoro - Alvin Laily Nankeni; Sri Muljaningsih (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
This study aims to analyze the potential economic sector in the Tuban, Lamongan, and Bojonegoro Regencies. These three areas are the Golden Triangle Region of Growth mentioned in the Regional Spatial Plan (RTRW) of the East Java Provincial Government in Law No. 26 of 2007. This study used a quantitative research method with Location Quotient, Shift Share, and Typology Klassen analytical tools. The data used in this study was the secondary data from the Central Bureau of Statistics (BPS) of Tuban, Lamongan, Bojonegoro Regencies, and East Java Province in 2016-2019. The study results showed ten potential sectors, including the mining and quarrying sector, processing industry sector, construction sector, wholesale and retail trade, car reparation, transportation and warehousing sector, and other services sectors not specified in these three regencies or the Golden Triangle Region of Growth. Meanwhile, Tuban and Bojonegoro regencies had sectors classified as fast-growing, and Lamongan Regency had developed and rapidly growing sectors.